2011
DOI: 10.1016/j.jvs.2010.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes for systematic primary stent placement in complex iliac artery occlusive disease classified according to Trans-Atlantic Inter-Society Consensus (TASC)-II

Abstract: Primary stent placement for complex iliac artery occlusive disease provides acceptable long-term outcomes, although the procedure takes relatively longer and is associated with a higher frequency of complications than for simple disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 21 publications
(27 reference statements)
5
46
1
3
Order By: Relevance
“…A low success rate of recanalization for occlusion in a long lesion has been reported previously, but the success rate has also recently increased due to improvement of therapeutic devices. 2, 13 The success rate of EVT for TASCII CD lesions is 89.8-95%, 14 which is similar in the present study (92.8%). In addition, the endovascular mortality was 0.3% and the 30-day mortality was 0.7% in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…A low success rate of recanalization for occlusion in a long lesion has been reported previously, but the success rate has also recently increased due to improvement of therapeutic devices. 2, 13 The success rate of EVT for TASCII CD lesions is 89.8-95%, 14 which is similar in the present study (92.8%). In addition, the endovascular mortality was 0.3% and the 30-day mortality was 0.7% in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, distal embolization following stent implantation was detected in four patients (7.4%). Other authors have reported distal embolization range to be from 2% to 13% [24][25][26].…”
Section: Discussionmentioning
confidence: 96%
“…Iliac artery stenting is a robust tool, with good short-and longterm patency rates, in managing aortoiliac PAOD. 16,17 Both PTA and stenting can be performed via a retrograde ipsilateral common femoral artery puncture or via a retrograde contralateral common femoral artery puncture.…”
Section: Endovascular Procedures In the Aortoiliac Regionmentioning
confidence: 99%